Asosiasi antara Set Kesempatan Investasi dengan Kebijakan Pendanaan Dan Dividen Perusahaan, serta Implikasinya pada Perubahan Harga Saham - Imam Subekti; Indra Wijaya Kusuma (The Indonesian Journal of Accounting Research, 2013)
The objectives of this study are to empirically examine the correlation between the investment opportunity set (IOS) values as firm growth proxy and realized firm growth, to investigate the association between  the investment opportunity set and corporate financing, and dividend policies, and to examine the difference of firms stock price classified by the investment opportunity set value. Five variables are used as firm growth indicator such as book value of plant, property, and equipment to assets ratio (PPE/BVA);  market to book of equity ratio (MVE/BVE);  price to earning ratio (P/E); market to book of assets ratio (MVA/BVA); and capital addition to book of assets ratio (CAP/BVA). These variables are analized by common factor analysis. Fourty growth firms and 40 no growth firms from 97 public firms at Jakarta Stock Exchange except banking and financing industry firms can be determined, based on common factor analysis. Spearman Rank Correlation was employed to examine the correlation between IOS values and realized growth firm.The empirical results show that the correlation between MVA/BVA, MVE/BVE, and CAP/BVA and realized growth firm are significantly positive, as expected. However, there are no the correlation between PPE/BVA and P/E ratio and realized growth firm, as not expected. Growth firms have lower financing, and  dividend policies than no growth firms. Nevertheless, classified  firms based on IOS values don’t affect changes of stock price, proxied by abnormal return. It means that investors hav not reacted yet to the signals. The multivariate test result shows that stock price is not affected by firm growth classification, return on asset, and dividend payout.